U siebie. Literacki obraz Górnego Śląska jako swojskiej, ale nieoswojonej przestrzeni pogranicza - Karolina Pospiszil (Postscriptum Polonistyczne)
Experience of living in borderlands is the most important Upper Silesian experience. Complicated geopolitical situation affects on Silesian history, local inhabitants’ identity, specific character of this place (periphery complex, pressure of ideological and cultural centres versus everyday relations with the Other, who often is homely and who is different from stereotypes disseminated by ideological centres are experienced here). Upper Silesia had to – and still has to – struggle with typical borderlands’ problems such as: borders’ inconstancy, feeling of homeliness, everyday relations with the Others, extreme ideologization, danger, fear, multiculturalism, other culture’s remains even after a resettlements and emigrations. All these problems are a great theme in literature about Upper Silesia, which is trying to describe and understand inconstancy and tragedy of the borderland.